Kebebasan wanita - Abdul Halim Abu-Syiqqah (Gema Insani Press, 1997)
Oen, Jil.1=c.1-2;Jil.2=c.1-4; Jil.3=c.1-3; Jil.4=c.1-3; Jil.5=c.1-3; Jil.6=c.1-3/tr, jil.1=c.3; jil.2=c.5; jil.3=c.4; jil.4=c.4; jil.5=c.4; jil.6=c.4/wk, jl.3=c.5/ tr, jil.4=c.5